Temporary and Permanent Migrant Selection: Theory and Evidence of Ability-Search Cost Dynamics - Joyce J Chen; Katrina Kosec; Valerie Mueller (Institute for the Study of Labor (IZA), 2016)
The migrant selection literature concentrates primarily on spatial patterns. This paper illustrates the implications of migration duration for patterns of selection by integrating two workhorses of the labor literature, a search model and a Roy model. Theory and empirics show temporary migrants are intermediately selected on education, with weaker selection on cognitive ability. Longer migration episodes lead to stronger positive selection on both education and ability, as its associated jobs involve finer employee-employer matching and offer greater returns to experience. Networks are more valuable for permanent migration, where search costs are higher. Labor market frictions explain observed complex network-skill interactions.
Keywords: J61; O15; 330; migration; search costs; networks; Pakistan